PECD study of a single-conformer molecule: a critical comparison of experiment and theory. Issue 7 (8th February 2022) - Catone, D.; Zema, N.; Prosperi, T.; Stener, M.; Decleva, P.; Nitti, P.; Turchini, S.
Abstract : Photoelectron circular dichroism (PECD) displays sensitivity to tiny conformational geometry modifications. The influence of rotating functional groups on PECD is confirmed through investigating norcamphor, a mono-conformer molecule. Abstract : In this work we address a specific experimental and theoretical question regarding the influence of a conformational population in the modeling of photoelectron circular dichroism (PECD) spectroscopy. In the past two decades, PECD has revealed a rich and complex phenomenology in molecular processes with unprecedented insight, especially in molecular geometry sensitivity. Since the early development of this spectroscopy, theory has pointed out the importance of conformer influence on PECD; in particular, the rotation of methyl groups was surprisingly found to be responsible for strong modulation of the PECD signal. Here, to advance understanding of the effect of rotations, we have chosen to study norcamphor, a single-conformer molecule, as a benchmark for a PECD comparison between experiment and theory at the density functional theory (DFT) and time-dependent density functional theory (TDDFT) levels. The excellent agreement between experimental data and theory for norcamphor sheds light on the influence of rotations and gives a solid explanation for the reasonable qualitative agreement in the PECD of camphor, where three methyl groups are added to the same molecular structure.